Evaluation of the oral toxicity of formaldehyde in rats - David, David; Arkerman, Hanslavina (Universa Medicina, 2008)
Formaldehyde is used in the production of plywood, particleboard, a wide variety of molded or extruded plastic items, and for preserving cadavers. Experimental posttest only control group design was used to determine the histopathological changes of rat stomach tissue exposed to formaldehyde for 12 weeks in thirty adult female Sprague-Dawley rats weighing 150–200 g. The animals were randomized into three groups, namely the control group, the treatment group given 4 mg/L of formaldehyde, and the group treated with 6 mg/L of formaldehyde. The results showed that there was a significant difference in the thickness of the mucous layer of the gastric fundus between the control group and the group treated with 6 mg/L (p = 0.011), and also a significant difference in the thickness of the mucous layer of the gastric fundus between both treatment groups (4 mg/L vs. 6 mg/L) (p = 0.003), indicating that there was necrosis of the superficial layers of the gastric mucosa due to high concentrations of formaldehyde. In histopathology sections from all groups, similar changes were observed in both treatment groups, in the form of vacuolar (hydropic) degeneration of gastric fundus glands. In conclusion, administration of formaldehyde in drinking-water for 12 weeks caused histopathologic effects on the gastric mucosa in rats.